Welfare effects of endogenous copyright enforcement: The case of digital goods - Markus Pasche (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
In case of digital goods such like music, intellectual property rights are typically not exerted by the creators (artists) but by intermediaries. Their profits, and therefore also the income of the artists, are endangered by copyright infringements (piracy). It is well known from static welfare analysis that to some extent piracy reduces the deadweight loss by limiting monopoly power and could therefore increase welfare. This paper contributes to the discussion by including the costs of law enforcement into the welfare analysis. Most models in the literature assume that law is enforced by governmental activities. In contrast, this paper considers that law enforcement is exerted by agents (e.g. lawyer chancellories, provider of screening technologies) which are also seen as intermediaries. The enforcement effort is there fore endogenously determined. It is shown that this will lead to suboptimal welfare outcomes. A social planner has to regulate punishment and enforcement effort to a moderate level. A more rigorous fight against piracy could only be justified by negative dynamic welfare effects due to a loss of creativity. However, there is no empirical evidence for that.
Keywords: D60; L12; K11; K42; 330; copyright; digital goods; intermediation; law enforcement; music; piracy; welfare